Application of thermoelectric cooler in temperature control system of space science experiment. (5th March 2020) - Guo, Dongcai; Sheng, Qiang; Dou, Xiangyu; Wang, Ze; Xie, Liyao; Yang, Bo
Highlights: Thermoelectric cooler (TEC) is suitable for spacecraft temperature control. Combined system of TEC and heat exchanger is proposed. The combined system performs better than TEC-alone system. Abstract: As an important mission of space stations and scientific satellites, space science experiment usually requires effective temperature control measures. Integrating heating and cooling capacities, thermoelectric cooler (TEC) is competent for this job attributed to the low complexity and high reliability. In this paper, two TEC systems are introduced, including direct temperature control system (DTCS) and environment temperature control system (ETCS). DTCS directly deals with the temperature control of the target element surface. The effects of the current and the heat sink (i.e. working liquid) temperature are analyzed under heating and cooling conditions respectively. ETCS deals with the temperature control of the entire environment surrounding the element. The element is indirectly heated or cooled by the ambient air. Depending on whether an additional intermediate air-to-liquid heat exchanger is consisted or not, ETCS can be further classified as TEC-HX system and TEC-alone system. The heat exchanger may improve the system performances. The effects of the liquid flow rate and heat exchanger efficiency on system performances are analyzed, providing guides for the design of the practical system.